SISTEM INFORMASI ABSENSI RFID BERBASIS WEB MENGGUNAKAN ESP32 DI PT DHARMA SENTOSA MARINDO - Chandra, Chandra; Amrizal, Amrizal (Computer Science and Industrial Engineering, 2023)
In today's era, human daily activities cannot be separated from the use of technology. One of them is business activities. PT Dharma Sentosa Marindo is a company engaged in the shipyard industry. So far, the attendance administration records at PT Dharma Sentosa Marindo still use paper media which are then processed and stored on a computer manually. This makes the attendance process slower and less accurate, causing delays in generating attendance reports. This study aims to design an attendance information system at PT Dharma Sentosa Marindo to increase the speed and accuracy of recording attendance administration at PT Dharma Sentosa Marindo. The system design method uses the scrum method which uses the principles of agile development methodology. The results of system testing using the blackbox testing method show that the designed system has run smoothly and as expected